2019
DOI: 10.1002/ijgo.13064
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Randomized controlled trial of the effect of bilateral uterine artery ligation during cesarean among women at risk of uterine atony

Abstract: ObjectiveTo assess the effectiveness of prophylactic bilateral uterine artery ligation (BUAL) in reducing the incidence of postpartum hemorrhage (PPH) during cesarean delivery among women at risk of uterine atony.MethodsA randomized clinical trial at Cairo University Maternity Hospital, Egypt, from December 2017 to December 2018. Women at risk of uterine atony undergoing scheduled or emergency cesarean were randomized to two groups. In the BUAL group, women underwent BUAL before placental delivery; in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Tariq et al and Khatoon et al have also found an increased incidence of uterine atony 75-90% to be responsible for PPH. 13,15 In this study the PPH was successfully controlled by uterine artery ligation with 96.1% had no postoperative complications. Consistently Wang CY et al 14 reported that the hemorrhage was controlled effectively among 8(88.9%) cases out of nine among females who were undergone bilateral HAL even their conditions was critical initially.…”
Section: Resultsmentioning
confidence: 55%
“…Tariq et al and Khatoon et al have also found an increased incidence of uterine atony 75-90% to be responsible for PPH. 13,15 In this study the PPH was successfully controlled by uterine artery ligation with 96.1% had no postoperative complications. Consistently Wang CY et al 14 reported that the hemorrhage was controlled effectively among 8(88.9%) cases out of nine among females who were undergone bilateral HAL even their conditions was critical initially.…”
Section: Resultsmentioning
confidence: 55%
“…They found that there were no significant differences in age, BMI, number of previous cesarean deliveries or parity (all p>0.05). 11 Similarly, Mohamed et al demonstrated that there was no significant difference between their studied groups regarding demographic characteristics. 12 BUAL is a quick and easy surgical procedure that can be coupled with uterotonics to prevent PPH in high-risk cases such as placenta previa.…”
Section: Discussionmentioning
confidence: 90%